Strategies for lipid-based nanocomposites with potential activity against Mycobacterium tuberculosis: Microbial resistance challenge and drug delivery trends - Hatae, Arthur Cavalcante [UNESP]; Roque-Borda, Cesar Augusto; Pavan, Fernando Rogério [UNESP] (Elsevier, 2023)
Mycobacterium tuberculosis (MTB), the causative agent of tuberculosis, stands as an immensely devastating and persistently relevant pathogen, claiming the lives of millions each year. This infectious bacterium remains a formidable global health challenge, necessitating urgent attention and comprehensive strategies to combat its profound impact on public health. MTB is a finicky bacterium that manages to sneak into macrophages and fibroblasts to avoid being eliminated. Current first-line treatments allow the control of the spread of an active MTB, but are not capable of effectively controlling when MTB is in its latent phase and struggle against MTB resistant strains. Lipid-based nanoparticles have gained significant attention in the field of tuberculosis nanotechnology treatments, owing to their compelling logical underpinnings, remarkable merits, and acknowledged demerits. These nanoparticles offer a rational approach by harnessing the unique properties of lipids, such as biocompatibility and stability, to encapsulate and protect anti-tuberculosis drugs. Their inherent ability to actively target infected macrophages holds immense promise for precise drug delivery to the infection site, enhancing therapeutic efficacy. However, it is crucial to consider potential limitations, such as the restricted payload capacity due to their small size and challenges in achieving sustained drug release. Despite these challenges, lipid-based nanotechnology represents an exciting frontier for combating drug resistance and advancing tuberculosis treatment strategies, warranting further exploration and development in this field. In addition, we emphasize the characteristics of lipid-based nanoparticles with the ability to improve the administration, stability, and dosage of these molecules. New modified systems are expected to be successful in the coming years as nanotechnology has improved various treatments in other diseases.
Keywords: Antimicrobial peptides; Bacteriophage; DNA vaccine; MTB; Nanotechnology